Human heparanase roles in invasion and metastasis of cancer - Gohji, K (Hinyokika kiyo. Acta urologica Japonica, 2000)
Heparanase, which is an extracellular matrix degradative enzyme, degrades heparan sulfate and heparan sulfate proteoglycans, which are chief components of extracellular matrix and vascular basement membrane. The gene structure of this enzyme was recently determined. The biological functions of this enzyme in vivo were as follows: 1) this enzyme accelerates cancer cell invasion and metastasis though the degradation of vascular basement membrane and extracellular matrix by cancer cells; 2) this enzyme releases and activates heparin-binding growth factors such as bFGF and VEGF from heparan sulfate proteoglycans, and induces angiogenesis; 3) the degradative products of heparan sulfate proteoglycans by this enzyme suppress the biological function of activated T-lymphocytes. Therefore, heparanase is thought to be a favorable molecule for acceleration of cancer invasion and metastasis. The expression of heparanase is strongly correlated with the metastasis of melanoma and fibrosarcoma. Thus, heparanase may play important roles in invasion and metastasis of cancer